(3MjGI GdMjhGf GdcHQis - (3eMeO Hf ehSi Hf YjSi Hf Ydj GdOejQj, CHh GdHbGA, ceGd GdOjf , (B808 (3g`s
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3YdeG Jdc abGd Ef OGfjGd faS UhQJg hUhQI GdCSOjfaj aU NGJeg djdG jfSi fYeI Gddg Ydjg aj Pdc GfJgis
(3BNQgG (B:s
(3bHQg CeS GdfGS Hg QMeG hgh CSQge HehJg abGd dg eYGhjI dbO QCjJ YLHG aef GdejJ bGd YKjQI Hf dHjO GdYPQj, BNQ GdLRA GdChds
(3aj BNQg eOM deDdaGJ GdOejQj ef HQgGf GdOjf CHh ESMb GdbjQGWjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 118s
(3eYLe GdeDdajf(B: 3 / 743s
(3cTa GdXfhf(B: 1 / 696s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs